Fabrication and performance of a novel polymer composite waterproof adhesive layer with enhanced hydrophobicity for concrete bridge decks - Bonan Ma; Fei Wang; Jiaqi Li; Chaodong Yang; Wentao Jia; Kaisheng Luo; Enhui Yang; Yanjun Qiu (Case Studies in Construction Materials)
The waterproof adhesive layer (WAL), as an integral part of concrete pavements, provides both waterproofing and bonding functions for concrete bridge decks. Due to advancements in construction technologies, long-span concrete bridges operating under harsh conditions have become more prevalent, raising the performance requirements for WAL. Therefore, this study develops a novel polymer composite waterproof adhesive layer (PCWAL) through hydrophobic modification and fiber reinforcement. We utilized epoxy resin (EP) and polyurethane (PU) as the matrix materials. Additionally, KH550-modified nano-SiO2 and polymethyltrifluoropropylsiloxane (PF) served as hydrophobic modifiers, while polypropylene fibers provided reinforcement. In this case, the PCWAL demonstrated high surface roughness (Sa = 3.355 μm), strong hydrophobicity (θ = 125.3°), and excellent impermeability. Furthermore, PCWAL exhibited outstanding thermal stability, flexibility at low temperatures, resistance to chemical corrosion, tensile strength, and deformation capacity. Watertightness, shear, and pull-off tests were conducted to evaluate PCWAL’s road performance under diverse environmental conditions. The watertightness test indicated that PCWAL has exceptional water resistance, with no leakage under 300 kPa. Even after prolonged water immersion, the reduction in bonding strength was minimal (less than 5 %). However, as temperatures increased, the bonding strength of the composite specimens decreased, with a sharp drop observed after freeze-thaw cycles. The fatigue test further revealed that PCWAL has a significantly longer fatigue life compared to asphalt-based WALs and maintains superior fatigue resistance under varying peak stress conditions. Consequently, it can be concluded that the PCWAL, with its excellent waterproofing and bonding performance under diverse environmental conditions, is expected to be a new practical WAL.